Development of a SETS-based e-module to enhance critical thinking skills on environmental change - Deslia Amanda; Suci Fajrina; Abdul Razak; Rahmawati Darussyamsu (University of Muhammadiyah Malang, 2025)
Environmental change is one of the most pressing issues in the 21st century, requiring students to develop strong critical thinking skills to understand and address its impacts. However, conventional biology learning in schools often remains teacher-centered and less connected to real-life contexts. This study aimed to develop a Science, Environment, Technology, and Society (SETS)-based e-module on environmental change material to enhance students’ critical thinking skills. The participants were 66 tenth-grade students at SMAN 1 Ranah Batahan, West Pasaman Regency, West Sumatra, divided into an experimental class (n = 33) and a control class (n = 33). Validation was conducted by two media experts and two material experts. The development followed the ADDIE model, including analysis, design, development, implementation, and evaluation stages. Research instruments consisted of validation sheets, practicality questionnaires, and critical thinking skill tests. The results showed that the e-module was highly valid (average 96.3%) and very practical (teachers: 97.1%; students: 92.5%). Effectiveness testing using a quasi-experimental design and independent t-test revealed a significant improvement in students’ critical thinking skills in the experimental class compared to the control class (p < 0.001). These findings highlight that SETS-based e-modules are effective learning media in biology education, as they connect scientific concepts with environmental, technological, and societal contexts while fostering the development of critical thinking skills essential for 21st-century education.